Precision therapeutic targets for COVID-19 - Zachary A. Krumm; Grace M. Lloyd; Connor Francis; Lith Nasif; Duane A. Mitchell; Todd E. Golde; Benoit I. Giasson; Yuxing Xia (2021)
Beginning in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged as a novel pathogen that causes coronavirus disease 2019 (COVID-19). SARS-CoV-2 has infected more than 111 million people worldwide and caused over 2.47 million deaths. Individuals infected with SARS-CoV-2 show symptoms of fever, cough, dyspnea, and fatigue with severe cases that can develop into pneumonia, myocarditis, acute respiratory distress syndrome, hypercoagulability, and even multi-organ failure. Current clinical management consists largely of supportive care as commonly administered treatments, including convalescent plasma, remdesivir, and high-dose glucocorticoids. These have demonstrated modest benefits in a small subset of hospitalized patients, with only dexamethasone showing demonstrable efficacy in reducing mortality and length of hospitalization. At this time, no SARS-CoV-2-specific antiviral drugs are available, although several vaccines have been approved for use in recent months. In this review, we will evaluate the efficacy of preclinical and clinical drugs that precisely target three different, essential steps of the SARS-CoV-2 replication cycle: the spike protein during entry, main protease (M